Possible predictors of functional prosthetic ambulation in adults with unilateral above-knee amputation in the Western-Cape - Bakkes, Elsje Sophia (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1999.